Сильфій пронизанолистий (Silphium perfoliatum L.) у Лісостепу України - Arkhipеnko, F.N.; Larina, V.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2011)
For securing the productive longevity of perfoliate compass-plant agrocoenosis in the condition of the northern Ukrainian Forest-Steppe on dark grey podzolized large-silty sandy loam soil at the double-cutting use regime it is nessesary to conduct the periodical application of phosphoric and potassic fertilizers when annually early-spring applied nitrogenous fertilizers. Date about the biochemical, macro- and microelement composition of dry matter are adduced.